Induction of complete courtship ritual in Amblyomma cajennense using 2,6-dichlorophenol at female-equivalent quantities - Gachoka,Kennedy Kiriira (2011)
In order to clarify the role of 2,6-dichlorophenol (2,6-DCP) in the courtship of Amblyomma cajennense, sexually mature males that had previously fed on rabbits were tested in bioassays. The males were released onto dummies treated with whole female extract or synthetic 2,6-DCP at a concentration of two female equivalents, or with hexane (control), and their responses were observed. In the presence of both the extract and 2,6-DCP, excitation was observed among the males, expressed in the form of touching and probing the dummy, and mounting occurred readily. The percentages of mounting (73%) and tipping over (60%) were equal in the two treatments and higher than in the control group (27 and 20%, respectively). Relatively short durations of mounting were recorded, and these were statistically similar in all treatments. Almost all instances of mounting resulted in tipping-over behavior. A few isolated cases of males that went directly to ventral positioning without mounting were observed. It was confirmed that 2,6-DCP alone is capable of mediation of mounting behavior in A. cajennense.